ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI BILANGAN - Muh. Akhyar Syam; Istifani, Nurul; Asriani; Syariah; Nurul Ainun Fajriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is a qualitative research aimed at describing student errors in solving numerical operation problems. Error analysis employs Newman's procedure which identifies five types of errors: reading, comprehension, transformation, process skills, and encoding. The research was conducted at MTS. Muh Maradekaya in grade VIII with three students as research subjects selected purposively based on criteria of being at the same grade level, attending the same school, and having a minimum test score of 75. The research instruments consisted of the researcher as the primary instrument, along with five essay test questions and interview guidelines as supporting instruments. Data analysis techniques employed the Miles and Huberman model including data reduction, data presentation, and data verification. Data validity was obtained through technical triangulation combining tests to identify student errors, interviews to explore the underlying factors causing errors, and documentation to record the research process and student work results. The research findings revealed that students made the most errors in the transformation information indicator. This condition indicates that student problems are not merely technical calculation issues, but also involve reading comprehension, understanding, and deep thinking abilities.